Beauty contests, Challenging Israeliness (ModaPalavra e-periódico, 2016)
In this article, I compare the “Israeli Beauty Queen” 2006 contest and “Miss Asia-Israel” 2006 contest as public events describing everyday Israel. Comparing both contests reflects the wider social and cultural transformations Israel is facing. Each pageant produces dominant imagens and narratives about whom and what ‘Israeli’ women are and should be while simultaneously narrating who and models of Israeliness embodied through the display of the female body.
Keywords: beauty pageants; female body; nationalism; public events; Israël